2006
DOI: 10.2320/matertrans.47.1546
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Microstructure and the Thermal Equilibrium Diagram of Au-Co Alloy Electrodeposit

Abstract: An Au-Co alloy with an extensive composition range was electrodeposited from a gold sulfite and cobalt sulfate mixture. The Au-Co alloy electrodeposits were analyzed by XRD and TEM and the relationship between the phase and thermal equilibrium diagrams was investigated. The Au-Co alloy electrodeposits formed a solid solution over an extensive composition range. It was also revealed that the composition of the electrodeposited Au-Co alloy was equal to that of the quenched phase at a high temperature, about 950 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Though these features indicated the characteristics of a AuCo intermetallic structure, the intensities of these particular peaks were weak and indicated that only a partially ordered alloy was formed. 27 Thus, the observed small shi in our case suggested that only a small part of the surface Co species has been alloyed with Au nanoparticles. In addition, neither Co nor CoO x phases were detected in the AuCo/MCF catalysts, suggesting that Co might exist as highly dispersed species.…”
Section: Catalytic Experimentsmentioning
confidence: 50%
“…Though these features indicated the characteristics of a AuCo intermetallic structure, the intensities of these particular peaks were weak and indicated that only a partially ordered alloy was formed. 27 Thus, the observed small shi in our case suggested that only a small part of the surface Co species has been alloyed with Au nanoparticles. In addition, neither Co nor CoO x phases were detected in the AuCo/MCF catalysts, suggesting that Co might exist as highly dispersed species.…”
Section: Catalytic Experimentsmentioning
confidence: 50%
“…Nowadays, the generation of bimetallic alloy particles has been investigated using chemical methods and the milling of powders. [9][10][11][12][13][14][15] However, the use of these methods may lead to contamination of the product as a result of chemical precursors or the abrasion of grinding elements. 16 A laser ablation-in-liquid technique is considered a safe, simple and versatile way to produce nanocrystals and nano-sized oxides.…”
mentioning
confidence: 99%
“…They found the structure of Au-Co alloy film were composed of cobalt supersaturated gold solid solution at cobalt content less than approximately 18.0 at.%, and gold supersaturated ε-Co solid solution at cobalt content above approximately 94.0 at.%. 20 Take the non-equilibrium process of electrodepositing into consideration, the diffraction peaks 1), (Au-JCPDS: 04-0784; Cu-JCPDS: 04-0836), respectively. Almost all patterns performed gold lattice, few cobalt diffraction peaks were found, as reported.…”
Section: Resultsmentioning
confidence: 99%
“…Different electrolyte composition will result in various Au-Co alloy electrodeposits. 19,20 SIII. SEM and a scanner were used to analysis micromorphology and micromorphology of electrodeposits, respectively.…”
Section: Methodsmentioning
confidence: 99%